Options for Aged Care in China : Building An Efficient and Sustainable Aged Care System - Glinskaya, Elena (Washington, DC: World Bank, 2018)
China is aging at an unprecedented rate. Improvements in life expectancy and the consequences of the decades-old family planning policy have led to a rapid increase in the elderly population. According to the United Nations World Population Prospects, the proportion of older people age 65 and over will increase by about one-fourth by 2030, and the elderly will account for about one quarter of the total population by 2050. Population aging will not only pose challenges for elder care but also have an impact on the economy and all aspects of society (World Bank, 2016a).